Implementation of Green Marketing Mix on Purchasing Decisions of MSME Products in Semarang City - A. Aini Yakiyatur R; Nur Wahyuni, Asri (Fakultas Ekonomi dan Bisnis, Telkom University., 2025)
This study aims to analyze the effect of Green Marketing Mix (Green Product, Green Price, Green Place, Green Promotion, Green People, Green Process, and Green Physical Evidence) on purchasing decisions for MSME products in Semarang City. The research method used is quantitative with purposive sampling and snowball sampling techniques, involving 100 respondents. The results showed that all elements of the green marketing mix have a positive and significant influence on purchasing decisions with green price, green promotion, and green physical evidence as the dominant factors. The originality of this research lies in the comprehensive analysis of the application of green marketing mix in the context of MSMEs in Semarang City, enriching insights into consumer behavior towards environmentally friendly products. The implications of this study encourage MSMEs to set competitive pricing strategies, increase green promotions through various media, and pay attention to aspects of physical evidence such as the use of recycled packaging and product appearance to attract consumers. Further research can be conducted by expanding the respondent segment or applying longitudinal methods to see changes in consumer preferences for green products over time.